Constraints on the origin of cosmic rays above 1018 ev from large-scale anisotropy searches in data of the pierre auger observatory - Abreu, P.; Aglietta, M.; Ahlers, M.; Ahn, E. J.; Albuquerque, I. F. M.; Allekotte, Ingomar; Almela, Daniel Alejandro; Arganda Carreras, Ernesto; Asorey, Hernán Gonzalo; Avila, G.; Bertou, Xavier Pierre Louis; Contreras, F.; et al. (American Astronomical Society, 2013)
Fil: Abreu, P.. Universidade Técnica de Lisboa; Portugal